Trend PNBP sektor kehutanan Provinsi Papua Barat pasca implementasi kebijakan si-puhh online dan self assesment - Yuli Triestini; Bambang Nugroho; Rima H.S. Siburian (Cassowary, 2020)
Changes in forest management policies by applying the Self-Assesment system, and online SI-PUHH are expected to affect the realization of PNBP for West Papua Province. How the PNBP Trends after implementing the policy in West Papua Province is a problem that will be answerd through this research. The study aims to determine trends and forecasting of PNBP Forestry Sector after the implementation of online self-assessment and SI-PUHH policies in West Papua Province. The realization of PNBP of West Papua Province originating from PSDH and DR during 2010 – 2018 shows an increasing trend even in certain years of decline. Fluctuations occur as a result of the enforcement of the self-assessment and SI-PUHH Online policies which often experience changes, especially the use of certain applications that are erquired.